Palmitoylated Prolactin-releasing Peptide Reduced Aβ Plaques and Microgliosis in the Cerebellum: APP/PS1 Mice Study - Mengr, Anna; Hrubá, Lucie; Exnerová, Aneta; Holubová, Martina; Popelová, Andrea; Železná, Blanka; Kuneš, Jaroslav; Maletínská, Lenka (Current Alzheimer research, 2021)
BACKGROUND: Prolactin-releasing peptide (PrRP) is a potential drug for the treatment of obesity and associated Type 2 Diabetes Mellitus (T2DM) due to its strong anorexigenic and antidiabetic properties. In our recent study, the lipidized PrRP analog palm11-PrRP31 was proven to exert beneficial effects in APP/PS1 mice, a model of Alzheimer´s Disease (AD)-like amyloid-β (Aβ) pathology, reducing the Aβ plaque load, microgliosis and astrocytosis in the hippocampus and cortex. OBJECTIVE: In this study, we focused on the neuroprotective and anti-inflammatory effects of palm11-PrRP31 and its possible impact on synaptogenesis in the cerebellum of APP/PS1 mice, because others have suggested that cerebellar Aβ plaques contribute to cognitive deficits in AD. METHODS: APP/PS1 mice were treated subcutaneously with palm11-PrRP31 for 2 months, then immunoblotting and immunohistochemistry were used to quantify pathological markers connected to AD, compared to control mice. RESULTS: In the cerebella of 8 months old APP/PS1 mice, we found widespread Aβ plaques surrounded by activated microglia detected by ionized calcium-binding adapter molecule (Iba1), but no increase in astrocytic marker Glial Fibrillary Acidic Protein (GFAP) compared to controls. Interestingly, no difference in both presynaptic markers syntaxin1A and postsynaptic marker spinophilin was registered between APP/PS1 and control mice. Palm11-PrRP31 treatment significantly reduced the Aβ plaque load and microgliosis in the cerebellum. Furthermore, palm11-PrRP31 increased synaptogenesis and attenuated neuroinflammation and apoptosis in the hippocampus of APP/PS1 mice. CONCLUSION: These results suggest palm11-PrRP31 is a promising agent for the treatment of neurodegenerative disorders.
Keywords: Cerebellum; Humans; APP/PS1 mice; Mice, Transgenic; palm11-PrRP31; hormon uvolňující prolaktin; myši transgenní; lidé; Alzheimer Disease; zvířata; Alzheimerova nemoc; myši; amyloidní beta-protein; Plaque, Amyloid; Mice; Prolactin-Releasing Hormone; Diabetes Mellitus, Type 2; presenilin-1; amyloid-β plaques; neuroinflammation; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Alzheimer's disease; mozeček; Presenilin-1; synaptogenesis.; amyloidový prekurzorový protein beta; Animals; cerebellum; diabetes mellitus 2. typu; Disease Models, Animal; amyloidní plaky; hippocampus; modely nemocí na zvířatech